The relationship between workplace support and job satisfaction amongst academic staffs in higher learning instituitions at five Public Research Universities in Malaysia / Muhammad Khawari Mustapa @ Awang - Mustapa @ Awang, Muhammad Khawari (Faculty of Office Management and Technology, 2016)
The present study aims to examine the relationship between workplace support and job satisfaction amongst academic staffs in higher learning educations at five Public Research Universities in Malaysia. The population of this study consists of 12,994 academic staffs and the sample size were 325 academic staffs. The sample was obtained using the convenience sampling technique, in which gathering of information from fellows of the population in the organizations who are conveniently available to obtain it. The workplace support was represented by four elements; perceived organizational support (POS), supervisor support, co-worker support and mentoring.